2014
DOI: 10.5897/ijbc2013.0662
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterization of shea tree (Vitellaria paradoxa subsp. paradoxa) populations in the region of Mandoul in Chad

Abstract: Quantitative characteristics of leaf, fruit and nut collected from Vitellaria paradoxa subsp. paradoxa growing in Kol, Kemkian and Matekaga located in the region of Mandoul of Southern Chad were analyzed. Our results reveal variation of the measured morphological parameters. The smallest lamina length (15.5 cm) was found in Kol and the longest (26.3 cm) in Matekaga. The biggest lamina width (5.4 cm) and nut length (3.8 cm) were found in Kol. Using the correlation matrix data, our investigations revealed that l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
1
9
1
1
Order By: Relevance
“…(Diallo et al, 2010), Jatropha curcas (Ly et al, 2014) et trois espèces de Chênes du genre Quercus (Sarir et Benmahioul, 2017). D'importantes variabilités avaient été également trouvées au niveau des arbres adultes du karité par Djekota et al (2014) au Tchad, Souberou et al (2015) au Benin et Sandwidi et al (2018a) au Burkina Faso dans un essai de provenances. De plus, des travaux sur les caractères morphologiques (feuilles et capsules) d'autres espèces adultes comme Adansonia digitata L. (Assogbadjo et al, 2006) ont montré des résultats similaires.…”
Section: Relation Entre Les Caractères Morphologiques Des Plantulesunclassified
“…(Diallo et al, 2010), Jatropha curcas (Ly et al, 2014) et trois espèces de Chênes du genre Quercus (Sarir et Benmahioul, 2017). D'importantes variabilités avaient été également trouvées au niveau des arbres adultes du karité par Djekota et al (2014) au Tchad, Souberou et al (2015) au Benin et Sandwidi et al (2018a) au Burkina Faso dans un essai de provenances. De plus, des travaux sur les caractères morphologiques (feuilles et capsules) d'autres espèces adultes comme Adansonia digitata L. (Assogbadjo et al, 2006) ont montré des résultats similaires.…”
Section: Relation Entre Les Caractères Morphologiques Des Plantulesunclassified
“…Many studies have shown the existence of a high intra-specific variation (Chevalier 1943;Ruyssen 1957) among shea trees. Many authors have also shown a phenotypic variation and a correlation between its different physical properties Lovett and Haq (2004) in Ghana, Sanou et al (2006) in Mali, Diarrassouba et al (2007) and Djekota et al (2014) in Chad. Therefore, a study on the shea diversity is necessary for a good conservation, good management and a selection of the best genetic resources of this tree species.…”
Section: Introductionmentioning
confidence: 97%
“…5000 km long, 500 to 700 km wide between 600 and 1500 mm isohyets (Hemsley, 1968;Boukoungou, 1987;Salle et al, 1991;Hall et al, 1996). Two subspecies have been identified presently (Djekota et al, 2014), V. paradoxa subsp. paradoxa is found in West and Central Africa (Salle et al, 1991;Fontaine et al, 2004;Sanou et al, 2005;Allal et al, 2008;Nyarko et al, 2012 while V. paradoxa subsp.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations